Сhoice of a thrombolytic for pulmonary thromboembolism treatment - Nykonenko, Olexander; Nykonenko, Andriy; Matvieiev, Serhii; Osaulenko, Viacheslav; Nakonechny, Serhii (ScienceRise: Medical Science, 2017)
Aim of the study was to choose the optimal thrombolytic therapy for massive and submassive TEPA. Materials and methods. 102 patients with massive and submassive embolism of lungs (Miller index > 17) were arbitrarily divided for administrating 100 mg of the recombinant tissue activator of plasminogen (r-tPA) or 3 mln of UN of streptokinase. The control multi-spiral computer tomography of breast organs (MSCT BO) or angiopulmonography (APG) was realized in 2–3 days after thrombolysis. For calculating the statistical importance of the difference of the number of patients by the concomitant pathology and sex, there was used χ2 with Ets correction. Mann-Whitney criterion was used for calculating the difference by age. Results. There was established the advantage of using r-tPA in hemodynamically unstable patients. There was established the advantage of using streptokinase in patients with the disease duration more than 1 day. There was proved the effectiveness of repeated sessions of thrombolysis. There was established, that it’s possible to prevent hemorrhagic complications of thrombolysis if to reveal its contraindications accurately. Conclusions. Alteplase must be used in hemodynamically unstable patients due to the faster effect comparing with streptokinase. Alteplase or streptokinase must be used for hemodynamically stable patients with massive and submassive pulmonary embolism. The repeated TLT is equally effective as thromboembolectomy at insufficient effectiveness of thrombolysis. For preventing hemorrhagic complications, the detail examination of patients is necessary to reveal possible sources of fatal bleeding and determination of contraindications to TLT